Role of Mitogen Activated Protein Kinase and Maturation Promoting Factor During the Achievement of Meiotic Competency in Mammalian Oocytes. Issue 1 (31st July 2017) - Tiwari, Meenakshi; Gupta, Anumegha; Sharma, Alka; Prasad, Shilpa; Pandey, Ashutosh N.; Yadav, Pramod K.; Pandey, Ajai K.; Shrivastav, Tulsidas G.; Chaube, Shail K.
ABSTRACT: The oocyte quality remains as one of the major problems associated with poor in vitro fertilization (IVF) rate and assisted reproductive technology (ART) failure worldwide. The oocyte quality is dependent on its meiotic maturation that begins inside the follicular microenvironment and gets completed at the time of ovulation in most of the mammalian species. Follicular oocytes are arrested at diplotene stage of first meiotic prophase. The resumption of meiosis from diplotene arrest, progression through metaphase‐I (M‐I) and further arrest at metaphase‐II (M‐II) are important physiological requirements for the achievement of meiotic competency in mammalian oocytes. The achievement of meiotic competency is dependent upon cyclic stabilization/destabilization of maturation promoting factor (MPF). The mitogen‐activated protein kinase3/1 (MAPK3/1) modulates stabilization/destabilization of MPF in oocyte by interacting either with signal molecules, transcription and post‐transcription factors in cumulus cells or cytostatic factors (CSFs) in oocyte. MPF regulates meiotic cell cycle progression from diplotene arrest to M‐II arrest and directly impacts oocyte quality. The MAPK3/1 activity is not reported during spontaneous meiotic resumption but its activity in cumulus cells is required for gonadotropin‐induced oocyte meiotic resumption. Although high MAPK3/1 activity is required for the maintenance of M‐II arrest in several mammalian species, its cross‐talk with MPF remains to be elucidated. Further studies are required to find out the MAPK3/1 activity and its impact on MPF destabilization/stabilization during achievement of meiotic competency, an important period that decides oocyte quality and directly impacts ARTs outcome in several mammalian species including human. J. Cell. Biochem. 119: 123–129, 2018. © 2017 Wiley Periodicals, Inc. Abstract : This review article updates information on the involvement of MAPK and MPF during the achievement of meiotic competency, a crucial period that determines the oocyte quality after ovulation that impacts assisted reproductive technology (ART) outcome in mammals.